Aggression and its Management - Sharma Choulagai, Poojan (Journal of Nursing Education of Nepal, 2011)
Aggression is associated with violent activities which occurs with most of the mentally ill patients. It arises from an innate drive or occurs as a defense mechanism and is manifested either by constructive or destructive acts directly towards self or others. Aggressive people ignore the rights of other people. They must fight for their own interests and they expect the same from others. An aggressive approach to life may lead to physical or verbal violence. The aggressive behavior often covers a basic lack of self confidence. The general objective of the article is to provide general guideline for nurses to manage the aggressive behavior of patients. Aggressive behavior can be managed by adopting soft and polite communication technique at first and at last, rapid tranquilization and restraining can be done.
Keywords: N/A